Numerical analysis of large elastoplastic deformations of bodies and continua and identification of their deformation diagrams under different types of loading - V.G. Bazhenov; E.V. Nagornykh (Учёные записки Казанского университета: Серия Физико-математические науки)
Based on the experimental-computational approach, a method for identifying deformation diagrams of elastoplastic materials by considering the inhomogeneity of the stress-strain state and large deformations was developed. Examples of the application of this method for various types of loading of the tested samples were presented: tension and torsion of cylindrical rods, kinetic indentation of a ball and a cylinder, dynamic compression of tablet samples, etc. A technique for interpolating the deformation diagram to take into account the type of stress state was proposed.